The Impact of Zinc Supplementation on the Course of Infections - Justyna Woźniak; Ewelina Kopczyńska; Piotr Kulej; Wiktor Biesiada; Justyna Weronika Kmieć; Anna-Mariia Chernysh; Aleksandra Dusińska; Jakub Waszczyński; Kamila Fuczyło; Karolina Stankevič (Quality in Sport)
Introduction Zinc plays a vital role in immune function, enhancing defense mechanisms and reducing infection duration and severity.